The essence of the Bank Guarantee Fund’s activity and related dilemmas in the context of banking system stability - Czechowska, Iwona Dorota (Annales. Etyka w Życiu Gospodarczym, 2019)
The deposit guarantee system in Poland was devised at the time of the economic transformation. Its creation resulted from a difficult situation in the banking sector, and so it was meant to be an antidote to clients’ problems associated with the insolvency of collapsing banks and with adjusting to European community law. The aim of this work is to present the Bank Guarantee Fund—an institution that is part of the financial safety net, whose main task is to protect the interest of depositors and to ensure the banking system’s stability. The paper looks at some aspects of the growing interest in bank deposit insurance schemes and lively discussions on the subject during a crisis in banking markets. In response to the crisis that started in the subprime lending market in the USA and spread to other segments of the financial markets as well as to other countries, the ECOFIN made a decision to increase the existing guarantee limits for individual persons and to speed up the payout of guaranteed funds. The above changes were aimed at strengthening the security of clients and increasing confidence in the banking sector.